Rejecting Early Eugenics: Illness and Futurity in Sofía Casanova's El doctor Wolski (1894). (2nd November 2021) - Rodriguez, Erika
Abstract: Despite constituting what is arguably the first representation of eugenics in Spanish literature, Sofía Casanova's El doctor Wolski (1894) has received little critical attention. Through contextual analysis and a disability studies approach, this article examines El doctor Wolski 's interrogation of medical genealogies and restrictions of reproductive rights, drawing attention to Casanova's awareness of the potential for eugenic initiatives to target women and the lower classes. The article concludes that El doctor Wolski not only anticipates the full-fledged eugenic debates that would develop in the following decades, but also refutes specific eugenic strategies and offers a vision of social progress that values ethics of care and includes a future for subjects with incurable illnesses.